2000
DOI: 10.1111/j.1151-2916.2000.tb01483.x
|View full text |Cite
|
Sign up to set email alerts
|

Glass Formation and Polyamorphism in Rare‐Earth Oxide–Aluminum Oxide Compositions

Abstract: compositions underwent a liquidliquid phase transition which resulted in glasses with a cloudy appearance due to spheroids of one glass in a matrix of a second glass. The two glasses were isocompositional within the limits of experimental error. Clear, brilliant, single-phase glasses were obtained from La 3 Al 5 O 12 , ErLaYAl 5 O 12 , and compositions containing >5 mol% La 2 O 3 substituted for the other rare-earth oxides. Formation of two glasses is attributed to nucleation and growth of the second liquid at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 21 publications
5
87
0
Order By: Relevance
“…The optical transparency of the sample increased with increasing glass forming ability because the number of micro-sized crystals, which act as a scattering center to visible light, was diminished. R. Webber et al [13] reported that the addition of the larger lanthanum (La) ion stabilizes the 4-coordinate Al 3+ (AlO 4…”
Section: Resultsmentioning
confidence: 99%
“…The optical transparency of the sample increased with increasing glass forming ability because the number of micro-sized crystals, which act as a scattering center to visible light, was diminished. R. Webber et al [13] reported that the addition of the larger lanthanum (La) ion stabilizes the 4-coordinate Al 3+ (AlO 4…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the eutectic or near eutectic compositions would give amorphous phase by rapid cooling (quenching). There exist no data in the system Al 2 O 3 -GdAlO 3 as far as we know, but Weber et al [19][20][21] reported amorphous formation in the system Al 2 O 3 -Y 2 O 3 by rapid quenching.…”
Section: Resultsmentioning
confidence: 94%
“…21 In this study, the melting point of the ALZ system reached 1665 • C. 22 Although the flame spray process provided a high temperature up to 3200 • C, only the smaller particles could be heated to a temperature above the melting point during the supersonic spray process. As shown in Fig.…”
Section: Preparation Of Alz Glass Powders By Flame Spraymentioning
confidence: 99%